1978
DOI: 10.1108/eum0000000004982
|View full text |Cite
|
Sign up to set email alerts
|

UK Consumers’ Attitudes towards Imports: The Measurement of National Stereotype Image

Abstract: The importance of variables such as price, promotional message, packaging and distribution policy in influencing consumer perceptions and attitudes towards products is well established. However, the additional information input of "Made in . . ." (i.e., the product's country of origin) has attracted little research attention in the United Kingdom, a fact which, in view of our changing status within the European community and the ensuing re-orientations in our international trade, suggests a fruitful course of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(159 citation statements)
references
References 4 publications
7
142
1
4
Order By: Relevance
“…Other researchers who were involved in the research of consumer ethnocentrism confirmed that male consumers tended to be less ethnocentric compared to women (Balabanis et al, 2001;Good & Huddleston, 1995;Sharma et al, 1995). Also there is a number of studies where no statistically significant effect of gender differences has been found (Caruana, 1996) and, again, some other studies show that men are more ethnocentric than women (Bannister & Saunders, 1978). The research of this phenomenon in Serbia in 2015 showed that men were more ethnocentric (Marinkovic et al, 2011, Gasevic et al, 2015, Grubor & Đokic, 2015.…”
Section: Theoretical Framework Of the Researchmentioning
confidence: 93%
“…Other researchers who were involved in the research of consumer ethnocentrism confirmed that male consumers tended to be less ethnocentric compared to women (Balabanis et al, 2001;Good & Huddleston, 1995;Sharma et al, 1995). Also there is a number of studies where no statistically significant effect of gender differences has been found (Caruana, 1996) and, again, some other studies show that men are more ethnocentric than women (Bannister & Saunders, 1978). The research of this phenomenon in Serbia in 2015 showed that men were more ethnocentric (Marinkovic et al, 2011, Gasevic et al, 2015, Grubor & Đokic, 2015.…”
Section: Theoretical Framework Of the Researchmentioning
confidence: 93%
“…The consumers' perception of a product significantly changes (for the better and for the worse) when they are told the country-of-origin of the product (Bannister and Saunders 1978). If the COO can influence consumers' perception of a product or service, then improving the image portrayed through the COO should be positioned to increase the number of foreign consumers.…”
Section: National Characteristics and National Identitymentioning
confidence: 99%
“…Several empirical investigations differ in industrialized countries and developing countries. In particular, different perceptions of manufactured products occurred in developed and developing countries [13,29,30]. There are indeed many preconceptions observed in developing countries [8,20,23].…”
Section: Country Of Originmentioning
confidence: 99%
“…According to Baker and Ballington [8], De Nisco [9], De Luca and Pegan [10], Bursi et al [11], the COO effect influences the consumer's decision-making process. Several studies have been proposed with this purpose for general products [12][13][14], for the commodity class of products [15], for specific products [16][17][18], and for particular brands [19,20]. The COO effect is dominant when the consumer associates the manufactured goods with the tradition of production [21,22].…”
Section: Country Of Originmentioning
confidence: 99%